Effectiveness of Parenteral Glutamine on Methotrexate-induced Oral Mucositis in Children with Acute Lymphoblastic Leukemia. (4th July 2017) - Chang, Yu-Hsiang; Yu, Ming-Sun; Wu, Kang-Hsi; Hsu, Mao-Chou; Chiou, Yee-Hsuan; Wu, Han-Ping; Peng, Ching-Tien; Chao, Yu-Hua
ABSTRACT: High-dose methotrexate (HDMTX) is important for children with acute lymphoblastic leukemia (ALL). There is no effective treatment for patients with oral mucositis, which is a major side effect associated with HDMTX. Here, we reviewed the medical records of patients younger than 18 yr with newly diagnosed ALL in our hospitals from 2002 to 2013. According to the nationwide protocol (TPOG-ALL-2002), each patient received four courses of HDMTX (2.5 or 5 g/m 2 ) during consolidation therapy. HDMTX courses with glutamine therapy were as the glutamine group, and intravenous glutamine (0.4 g/kg/day) was started within 48 h after the initiation of HDMTX for 3 consecutive days. HDMTX courses without glutamine were as the control group. A total of 347 HDMTX courses were administrated in the 96 children with ALL during the study period. The incidence of oral mucositis was significantly lower in the glutamine group than in the control group (3.8% vs. 17.6%; P = 0.004). In the glutamine group, no patients suffered from severe oral mucositis. No severe adverse effects associated with glutamine administration were noted. Accordingly, parenteral glutamine appears to be feasible and safe to prevent oral mucositis in patients receiving HDMTX.